THE FALL OF PUBLIC RELATION OFFICER AND THE RISE OF INFLUENCER IN THE INDONESIAN GOVERNMENT - Dani Fadillah; Arif Ardy Wibowo (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The presence of Public Relations Officers in the organization is a must because they’re responsible for establishing good relations between the organization and stakeholders. Good relations between these two will result in harmony. This is a key factor in the success of various programs implemented by the organization. However, it seems that now the role of Public Relations Officers of the Republic of Indonesia Government has begun to decline and be replaced by Influencers starting from the end of 2019 to mid-2020. This research is a case study to describe how the Public Relations Officer of the government of the Republic of Indonesia lost its main function, being heavily replaced by influencers promoting Omnibus Law on social media. Influencers can be a respectable profession if they maintain their quality as public communicators. First, influencers need to have qualifications and competencies relevant to their field. Second, influencers hired by government agencies openly convey to the public that the message sent is a form of a commercial public campaign. Third, government agencies that use influencer services also need to meet the qualifications and competency standards of the influencers they choose. The conclusion is that the government prefers to maximize the function of influencers so that the Omnibus Law gets support from the community rather than maximizing Public Relations Officer. However, the use of influencers must be accompanied by good communication. With this, we can hope that the influencers will develop into a public communication actor that is respectable and acceptable.